Implementasi Media Diorama dalam Meningkatkan Kreativitas Siswa - Muhammad Mushfi El Iq Bali; Siti Fatimatuz Zahroh (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to increase student creativity by implementing diorama media so that students can learn optimally. This descriptive research uses a qualitative approach using exploration or research strategies that produce interesting information. The data for this research is derived from both primary and secondary sources. Primary data sources predominantly encompass interviews conducted with school principals, homeroom teachers, and regular teachers. Additionally, secondary data can be acquired through the means of observations and document analysis. Various data collection methods are employed in this study, which include interviews, observations, and document analysis. The research outcomes facilitate the identification of four crucial aspects concerning the implementation of diorama media. Initially, identify the application of educational media in the sixth grade. Subsequently, develop diorama media with a focus on environmental conservation. Third, carry out the trial process of diorama media, emphasizing environmental care in the sixth grade. Fourth, reflection to produce designs and improve the practical implementation of solutions. Based on the results of this research, the implementation of diorama media carried out on sixth-grade students at Madrasah Ibtidaiyah Az-Zainiyah III can increase students' enthusiasm for learning and increase their creativity so that in learning students not only act as listeners but can also express their opinions through media that can be studied.